1979
DOI: 10.1177/036354657900700409
|View full text |Cite
|
Sign up to set email alerts
|

Tennis injuries: prevention and treatment

Abstract: When players are engaged in the sport of tennis, injuries may occur to the eyes, in the neck, to the shoulder and back, arm and elbow, wrist and hand, and feet. The key to prevention and treatment of these injuries is good coaching and a formal stretching and strengthening program. The drooped "tennis shoulder" of professionals and senior tennis players is a natural response to heavy use. Shoulder elevating exercises are useful when soreness is associated. The treatment of tennis elbow includes wrist extensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…Çeşitli araştırmacılar kas kuvveti ölçmek için farklı yöntemler kullanmışlardır. Ancak sonuçta hepside kasın ulaştığı maksimal kuvvetin ne kadar olduğunu bulmaya yöneliktir (6,7). Kimisi sporcuların kas kuvvetlerini bulmak amacıyla manuel kas testini, kimisi biodex dinamometreyi kullanmıştır.…”
Section: Discussionunclassified
“…Çeşitli araştırmacılar kas kuvveti ölçmek için farklı yöntemler kullanmışlardır. Ancak sonuçta hepside kasın ulaştığı maksimal kuvvetin ne kadar olduğunu bulmaya yöneliktir (6,7). Kimisi sporcuların kas kuvvetlerini bulmak amacıyla manuel kas testini, kimisi biodex dinamometreyi kullanmıştır.…”
Section: Discussionunclassified
“…Other authors have reported signifi cantly fewer knee injuries among senior players who play on clay surfaces than among those who play on hard courts. 35,36 In contrast, no signifi cant correlations between type of training (weight lifting, plyometric exercises, and no weight training or plyometrics) and patellar tendinopathy were found. That was a limited study, however, looking at only 2 types of training.…”
Section: Extrinsic Factorsmentioning
confidence: 92%
“…The severity of a slip can be determined by the distance which the shoe moves relative to the surface [5] which will be dependent on the traction force developed at the shoe-surface interface. Clay surfaces have been reported to have a lower occurrence of injury, compared with acrylic hard court surfaces [6][7][8][9][10]. This has partly been attributed to inherent differing styles of play on each surface caused by differences in ball speed and bounce [6].…”
Section: Importance Of Understanding Shoe-surface Traction In Tennismentioning
confidence: 99%